2010
DOI: 10.1038/jhg.2010.97
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association analysis of copy number variations in subarachnoid aneurysmal hemorrhage

Abstract: Subarachnoid aneurysmal hemorrhage (SAH) due to cerebral aneurysm rupture is a very serious disease resulting in high mortality rate. It has been known that genetic factors are involved in the risk of SAH. A recent breakthrough in genomic variation called copy number variation (CNV) has been revealed to be involved in risks of human diseases. In this study, we hypothesized that CNVs can predict the risk of SAH. We used the Illumina HumanHap300 BeadChip (317 503 markers) to genotype 497 individuals in a Japanes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 33 publications
0
4
0
7
Order By: Relevance
“…CNV can contribute to disease susceptibility by influencing the gene expression level [11] . CNV has been revealed to be associated with complex human diseases including autism, inflammatory autoimmune disorders, lung cancer, osteoporosis, subarachnoid aneurysmal hemorrhage, sporadic amyotrophic lateral sclerosis, avellino corneal dystrophy, and schizophrenia [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] . Recent studies have focused on how CNV in the human genome affects various inherited phenotypes, including disease susceptibility [22] , [23] .…”
Section: Introductionmentioning
confidence: 99%
“…CNV can contribute to disease susceptibility by influencing the gene expression level [11] . CNV has been revealed to be associated with complex human diseases including autism, inflammatory autoimmune disorders, lung cancer, osteoporosis, subarachnoid aneurysmal hemorrhage, sporadic amyotrophic lateral sclerosis, avellino corneal dystrophy, and schizophrenia [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] . Recent studies have focused on how CNV in the human genome affects various inherited phenotypes, including disease susceptibility [22] , [23] .…”
Section: Introductionmentioning
confidence: 99%
“…In another study, high-density (300K Illumina) SNP-microarrays from a GWAS of 191 Japanese patients with aneurysmal subarachnoid hemorrhage and 282 controls were used for CNV exploration. 45 CNV-findings were carefully validated by visual examination of the genoplot images and overlapping analysis with the Database of Genomic Variants (DGV - http://dgv.tcag.ca/dgv/app/home ). Moreover, selected findings were validated by quantitative PCR.…”
Section: Cnv In Stroke Patientsmentioning
confidence: 99%
“…They hypothesized that CNVs can predict the risk of SAH [47]. The authors identified a total of 4.574 CNVs from a Japanese population sample ( n  = 473) and discovered 1.644 unique CNV regions containing 1.232 genes.…”
Section: Cnvs In Hemorrhagic Strokementioning
confidence: 99%